2021
DOI: 10.1111/bjh.17441
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibody response to SARS‐CoV‐2 following asymptomatic infection in patients with plasma cell disorders on immunomodulatory therapy

Abstract: Patients with multiple myeloma and related plasma cell disorders (PCD) are considered extremely vulnerable to SARS-CoV-2 infection due to disease-related impaired humoral and cellular immunity as well as receipt of immunosuppressive therapy. 1 Overall mortality from COVID-19 disease in 650 PCD patients across 10 countries was 33%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A clinical audit was conducted at University College London Hospitals between December 2020 and July 2021 of anti‐spike protein antibody testing in patients with PCDs after each vaccine dose. Some had routine nucleocapsid antibody monitoring, 7 those receiving chemo‐immunotherapy (CIT) have 4‐weekly routine swabs. Patient and treatment characteristics were retrieved from medical records (Table SI ).…”
mentioning
confidence: 99%
“…A clinical audit was conducted at University College London Hospitals between December 2020 and July 2021 of anti‐spike protein antibody testing in patients with PCDs after each vaccine dose. Some had routine nucleocapsid antibody monitoring, 7 those receiving chemo‐immunotherapy (CIT) have 4‐weekly routine swabs. Patient and treatment characteristics were retrieved from medical records (Table SI ).…”
mentioning
confidence: 99%
“…The breadth of immune response against SARS-CoV-2 variants is also wider following infection than after vaccination [ 129 ]. Studies have shown mixed results regarding the serological response following COVID-19 in patients with plasma cell dyscrasias [ 130 , 131 ]. Interestingly, SARS-CoV-2 infection may induce superior humoral responses compared to the initial two-dose vaccination scheme in patients with MM on active treatment [ 132 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cancer patients, including those with hematological malignancies [ 2 , 3 ] such as multiple myeloma (MM) and other plasma cell disorders (PCD) [ 4 ], have a higher risk for a severe outcome following infection with SARS-CoV-2 [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%